ENHANCING ECONOMIC COMPETITIVENESS THROUGH THE DEVELOPMENT OF INDUSTRY IN THE REGIONS - Juraev, Sherzod; Egamberdiev, Farmonqul; Muminov, Nozim; Egamberdieva, Lola (International Journal of Psychosocial Rehabilitation, 2020)
The article develops recommendations for improving the regional structure of industry, taking into account the characteristics, natural and socio-economic opportunities and the environmental situation of the country's regions. The current state of industrial integration in the regions and related problems, the formation of the republic’s industry, the economic and geographical assessment of the factors influencing it, as well as scientific and practical proposals and recommendations for improving the regional and sectoral structure of the industry were also determined.